Understanding end times prophecy a comprehensive approach - Benware, Paul N. 1942- (Chicago, IL Moody, 1995)
Includes bibliographical references and indexes.
Keywords: Bible. Prophetic writings -- criticism, interpretation, etc; Dispensational premillennialism; Eschatology -- perspectives